2020
DOI: 10.1371/journal.pone.0238628
|View full text |Cite
|
Sign up to set email alerts
|

Stability of misoprostol tablets collected in Malawi and Rwanda: Importance of intact primary packaging

Abstract: Misoprostol is listed in the WHO essential medicines list and can be used for induction of labour, for prevention and treatment of post-partum haemorrhage, and for abortions. The compound is unstable, and substandard misoprostol preparations have been detected in low-and middle-income countries. We now investigated the stability of misoprostol tablets according to the international guidelines for stability testing of pharmaceutical products. Three brands (four batches) of misoprostol tablets were collected in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 23 publications
0
7
0
Order By: Relevance
“…Blister packaging offers additional protection to tablet and capsule dosage units through prevention of direct contact with atmospheric air, humidity and sunlight; which are the major factors that facilitate the deterioration of medicines on storage [ 37 39 ]. Our results provide further evidence on this, as it was found that medicine samples that used blisters for primary packaging were of significantly better quality as compared to those that used bottles for primary packaging.…”
Section: Discussionmentioning
confidence: 99%
“…Blister packaging offers additional protection to tablet and capsule dosage units through prevention of direct contact with atmospheric air, humidity and sunlight; which are the major factors that facilitate the deterioration of medicines on storage [ 37 39 ]. Our results provide further evidence on this, as it was found that medicine samples that used blisters for primary packaging were of significantly better quality as compared to those that used bottles for primary packaging.…”
Section: Discussionmentioning
confidence: 99%
“…10 Oxytocin is relatively inexpensive but requires refrigerated storage, electronic infusion pumps, and continuous electronic fetal monitoring by trained staff. [11][12][13] Dinoprostone also needs refrigeration and is more expensive than oxytocin or misoprostol. 8,14 Misoprostol is widely available in many LMICs as quality-assured generic tablets (25, 50, 100, and 200 μg).…”
Section: Introductionmentioning
confidence: 99%
“…Dinoprostone also needs refrigeration and is more expensive than oxytocin or misoprostol 8,14 . Misoprostol is widely available in many LMICs as quality‐assured generic tablets (25, 50, 100, and 200 μg) 11 . Misoprostol is cheaper than dinoprostone and does not require refrigerated storage, making it better‐suited for labor induction in resource‐constrained, high‐volume obstetric settings 8,12,14 …”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations